Glomus Tympanicum: A rare case of a painful bleeding ear - Boon Han Kevin Ng; Ing Ping Tang (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2017)
Glomus tympanicum is a rare tumor of the middle ear which typically present with pulsatile tinnitus, hearing loss and bleeding. Examination may reveal a vascular mass which bleed on contact. Imaging is important prior to surgical resection.  Statement of the problem: Here we present a rare case of a young man who presented with left ear bleeding and otalgia.  Result: Examination and imaging showed a vascular mass in the left external ear canal, left middle ear and involving the surrounding structures.  Conclusion: A differential of glomus tympanicum must be considered in cases which present with bleeding left external auditory canal mass and otalgia, although the most common presentations are hearing loss and tinnitus.